Simulation of in vitro water deficit for selecting drought-tolerant banana genotypes - Marssaro, Alice Lichs; Morais-Lino, Lucymeire Souza; Cruz, Jailson Lopes; Ledo, Carlos Alberto da Silva; Santos-Serejo, Janay Almeida dos (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to determine a method to simulate water stress in vitro to select drought-tolerant banana (Musa sp.) genotypes. The BRS Tropical and Prata Anã cultivars were grown in vitro in an MS liquid medium containing sucrose and benzylaminopurine (BAP), supplemented with different concentrations of polyethylene glycol (PEG) or sorbitol. The yield stability index of dry matter was evaluated. Cultivation for 30 days in a medium containing 15 g L-1 PEG or 36.4 g L-1 sorbitol is appropriate to simulate water stress in vitro.